PENINGKATAN KESIAPAN GURU INFORMATIKA KABUPATEN MAGELANG UNTUK MENGIMPLEMENTASIKAN MATA PELAJARAN INFORMATIKA DALAM KURIKULUM MERDEKA - Rosa, Paulina H. Prima (Universitas Sanata Dharma, 2023)
The importance of digital literacy and the challenges of the industrial revolution 4.0 that students must face are the main reasons why Informatics become one of subjects in Merdeka Curriculum taught at the junior and senior high school levels in Indonesia. However, in implementing the Merdeka Curriculum, especially the Informatics subject, there are still many schools and teachers who are not ready and do not understand the content and teaching materials of Informatics subjects which are very different from ICT subjects in the 2013 Curriculum. Therefore, the community service team of Informatics Study Program held training for Informatics teachers in Magelang Regency. 81 teachers participated in online and offline training and mentoring focused on 7 elements of informatics knowledge. The teacher training results showed that 36.4% of the participants thought the training activities helped, and 63.6% thought that the training activities beneficently improved their understanding of Informatics material in the Merdeka curriculum. In addition, 36.4% considered themselves more confident, 45.5% were ready, and 18.1% were quite ready about implementing the Informatics subject. As a follow-up, teachers still expect ongoing and more intensive assistance regarding computational thinking, algorithms and programming, cross-disciplinary practice and preparation of teaching materials.